2016
DOI: 10.1021/acs.nanolett.6b02331
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Emission of a Site-Controlled Single Quantum Dot from a Pyramidal Structure

Abstract: Emission control of a quantum emitter made of semiconductor materials is of significance in various optical applications. Specifically, the realization of efficient quantum emitters is important because typical semiconductor quantum dots are associated with low extraction efficiency levels due to their high refractive index contrast. Here, we report bright and unidirectional emission from a site-controlled InGaN quantum dot formed on the apex of a silver-coated GaN nanopyramidal structure. We show that the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The data are fit well using the three level system with an equation I(P)=I∞×P/(P+Ps), where () To study the effect of the PSS on the extraction efficiency, 3D finite difference time domain (FDTD) optical simulation (using Lumerical software) is carried out for the defect embedded in a pristine GaN and the one grown on a PSS. Based on the simulation results, the far field pattern and the collection efficiency can be obtained 25 . For the bare GaN substrate, a model consisting of a GaN layer (refractive index = 2.33) on top of sapphire layer (refractive index = 1.75) in an immersion oil environment (refractive index = 1.52) is assumed.…”
mentioning
confidence: 99%
“…The data are fit well using the three level system with an equation I(P)=I∞×P/(P+Ps), where () To study the effect of the PSS on the extraction efficiency, 3D finite difference time domain (FDTD) optical simulation (using Lumerical software) is carried out for the defect embedded in a pristine GaN and the one grown on a PSS. Based on the simulation results, the far field pattern and the collection efficiency can be obtained 25 . For the bare GaN substrate, a model consisting of a GaN layer (refractive index = 2.33) on top of sapphire layer (refractive index = 1.75) in an immersion oil environment (refractive index = 1.52) is assumed.…”
mentioning
confidence: 99%
“…Plasmonic nanoantennas are advantageous among a variety of optical resonators due to their broad spectral resonances, which make spectral matching between the optical mode and an emitter substantially less complicated. 3,[16][17][18] Although plasmonic resonances have low Qfactors compared with dielectric cavities, they provide high Purcell enhancements due to small mode volumes, 3,19 also known as 'hot spots'. Several techniques including electron beam lithography, 20 optical trapping of quantum emitters on top of metal nanoantennas 21 and wet chemical transfer 17 have been previously explored for deterministic assembly of hybrid quantum nanophotonic-plasmonic devices.…”
mentioning
confidence: 99%
“…In our more recent work, we have also suggested that site-controlled QDs in nanopyramid structures can be used as a unidirectional single-photon source. 5 To thus realize downward-guided emitted light from a QD, we conformally deposited silver films on the nanopyramids. We also confirmed numerically that the QD at the apex exhibited unidirectional emission toward the bottom of the structure (see Figure 3).…”
Section: 1117/21201612006808 Page 3/4mentioning
confidence: 99%
“…Specifically, we (top) and lower (bottom) hemispheres-from a single QD in a pyramidal structure (depicted center) that is covered by a conformally deposited Ag film. 5 : Wavelength. E: Energy.…”
mentioning
confidence: 99%